ІНФОРМАЦІЙНА ДІЯЛЬНІСТЬ ТА ІНФОРМАЦІЙНЕ ЗАБЕЗПЕЧЕННЯ ДІЯЛЬНОСТІ АДВОКАТА В УКРАЇНІ (World Science, 2020)
The scientific article analyzes the problems of legislation governing the activity of the Advocacy and in the field of disclosure of technologies in the provision of services of protection, representation and other types of legal assistance to the client in providing legal information, drafting procedural and other legal documents aimed at ensuring the realization of the client's rights, freedoms and legitimate interests.The directions of reforming the law in the sphere of advocacy by amending the Law of Ukraine of introducing the latest rules of law that will regulate modern public relations with regard to information and communication technologies are proposed.